"CLINICAL SURVEY OF HYGIENIC CONDITIONS AND CHANGES OF THE GINGIVAL ENLARGEMENT IN EPILEPTIC PATIENTS UNDER PHENYTOIN TREATMENT " - F. Mousavi (Tehran University of Medical Sciences, 1991)
A clinical study was made on epileptic patients in the diagnostic department of the Tehran School of Dentistry. The results showed that not all of the epileptic patients who are under control with phenytoin develop hyperplasia, and those who do not care about their oral health and hygiene will be afflicted by hyperplasia of gum. On the basis of patients, records gingival hyperplasia in most patients begins to appear 3-4 months after using the drug for the first time, progressing fully after 1.5-2 years. The dosage of the drug may have a role in the extent of the lesion. And it seems that young patients are at a higher risk.